(untitled) (International Journal of Engineering and Computer Science, 2014)
Wall painting restoration is the process of restoring old and damaged wall painting which have cracks, fold marks ,dark or white spots etc. back to their original or a near-original state. Restoration wall painting is a process of recover the wall painting which are corrupted by many natural phenomena like unfavourable weather conditions, dust, smoke etc. due to which the wall paintings affected by many problems like cracks. To overcome these limitations a new algorithm that is nearest neighbour algorithm is used that can serve both the tasks of detecting and removing the cracks, so the quality of the wall painting images can be improved. For more improvement in the quality of digital wall painting ,another deformity is considered that is white spots which are detected as well as removed and nearest neighbour algorithm is improved by increasing the contrast and saturation. The nearest neighbour algorithm provide the more accurate result as compared to SIHF algorithm based on parameters that are Peak signal to noise ratio (PSNR) and mean squared error (MSE). The nearest neighbour algorithm gives the more accurate results than the SIHF algorithm as it remove the more number of cracks and white spots.